2017
DOI: 10.1111/crj.12626
|View full text |Cite
|
Sign up to set email alerts
|

Red cell distribution width and uric acid in patients with obstructive sleep apnea

Abstract: Elevated levels of SUA and RDW were associated with OSA severity, as defined by AHI. In addition, RDW was significantly higher in severe OSA with CVDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 37 publications
0
19
1
Order By: Relevance
“…After screening, 35 studies were full-text reviewed for eligibility. Finally 17 studies (19,20,22,23,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) met the inclusion criteria and were included in this metaanalysis. The detailed steps of the study identification process are shown in Figure 1.…”
Section: Studies Identification and Characteristicmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening, 35 studies were full-text reviewed for eligibility. Finally 17 studies (19,20,22,23,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) met the inclusion criteria and were included in this metaanalysis. The detailed steps of the study identification process are shown in Figure 1.…”
Section: Studies Identification and Characteristicmentioning
confidence: 99%
“…And there was a gradual rising trend from mild OSAS (WMD =9.34, 95% CI: 1.79 to 16.88, P=0.02), moderate OSAS (WMD =12.66, 95% CI: 2.35 to 22.97, P=0.02) to severe OSAS (WMD =39.43, 95% CI: 32.19 to 46.67, P<0.00001). And moderate OSAS group (I 2 =23.4%, P=0.253) had low heterogeneity while mild and moderate OSAS group didn't have heterogeneity (I 2 =0.0%) (Figure 3C).RDWA total of 1,701 subjects were enrolled from 5 studies(29)(30)(31)(32)40), of which 381 were allocated to the mild OSAS group, 320 to the moderate OSAS group, 547 to the severe OSAS group and 453 to the control group. Mean RDWs were 14.46%, 14.56%, 14.72% and 15.32% in control, mild, moderate and severe OSAS groups (Table S3).…”
mentioning
confidence: 99%
“…Accordingly, studies assessing the daily habits of the paediatric population and their relationship with OSA should be planned, as well as the therapeutic capacity of physical activity. In this line, RDW has been associated with OSA severity in adult population [36], and has been suggested to be the only parameter related to comorbidities and their reversibility, due to its close relationship with the systemic inflammatory damage and with the vascular system [37].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive erythrocyte proliferation and apoptosis of HAPC may contribute to increased uric acid levels (12). Hyperuricemia is also commonly found in patients with erythrocytosis secondary to lung diseases and polycythemia vera (13,14), which indirectly indicates the correlation between erythrocytosis and uric acid. Moreover, the ltration function of the kidneys can be inhibited by increased blood viscosity.…”
Section: Discussionmentioning
confidence: 99%